2023
DOI: 10.14366/usg.22107
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of two-dimensional shear wave elastography in diagnosing hepatic veno-occlusive disease in pediatric patients undergoing hematopoietic stem cell transplantation

Abstract: Purpose: To evaluate the usefulness of two-dimensional shear wave elastography (2D-SWE) in diagnosing hepatic veno-occlusive disease (VOD) in pediatric patients.Methods: This study retrospectively included pediatric patients who underwent hematopoietic stem cell transplantation (HSCT) between November 2019 and January 2021. All 34 patients (8.7 ± 5.0 years) were examined using 2D-SWE for an initial diagnosis. Subgroup analysis was performed using the data from follow-up examinations of patients diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…The conditioning regimens can induce toxic damage to sinusoidal endothelial cells, resulting in local inflammation and migration of blood cells into the space of Disse, causing obstruction of the sinusoidal microcirculation, which can result in sinusoidal portal hypertension [ 3 , 15 , 19 ]. A recent retrospective study utilized SWE to diagnose veno-occlusive disease in pediatric patients [ 21 ], and found that a liver stiffness of 7.2 kPa or greater had a sensitivity of 84.2% and a specificity of 93.3% in differentiating veno-occlusive disease from non-veno-occlusive disease. However, due to its retrospective design, the study had inherent limitations, such as the absence of baseline SWE values before hematopoietic stem cell transplantation and irregular follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditioning regimens can induce toxic damage to sinusoidal endothelial cells, resulting in local inflammation and migration of blood cells into the space of Disse, causing obstruction of the sinusoidal microcirculation, which can result in sinusoidal portal hypertension [ 3 , 15 , 19 ]. A recent retrospective study utilized SWE to diagnose veno-occlusive disease in pediatric patients [ 21 ], and found that a liver stiffness of 7.2 kPa or greater had a sensitivity of 84.2% and a specificity of 93.3% in differentiating veno-occlusive disease from non-veno-occlusive disease. However, due to its retrospective design, the study had inherent limitations, such as the absence of baseline SWE values before hematopoietic stem cell transplantation and irregular follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…However, liver stiffness measured by SWE may be increased not solely due to fibrosis but to various other conditions, including inflammation, congestion, portal hypertension, and cholestasis [ 6 ]. Therefore, SWE can aid in the early detection of patients with suspected veno-occlusive disease [ 15 21 ]. Shear-wave dispersion (SWD) imaging reveals the shear wave slope, reflecting the viscosity associated with cellular inflammation, edema, and necrosis, providing a more comprehensive assessment of tissue characteristics compared to conventional US methods [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%